Self-neglect among older adults with disabilities in Liaoning Province during the COVID-19 outbreak: A cross-sectional study - Dong, Li; Sun, Longfeng (Frontiers in Psychology, 2022)
Background Self-neglect among older adults is a well-recognized public health issue. During the novel coronavirus disease 2019 (COVID-19), older adults with disabilities may be at increased risk for self-neglect. This study aimed to assess the prevalence of self-neglect and associated factors among older adults with disabilities in Liaoning Province during the COVID-19 outbreak. Methods A cross-sectional study was conducted from January 2021 to April 2021. A convenience sample of 230 older adults with disabilities filled out questionnaires that collected data on socioeconomic and demographic characteristics alongside data using the Barthel Index (BI), the Elder Self-Neglect Assessment (ESNA), the Geriatric Depression Scale-Short Form (GDS-SF), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Mini-Mental State Examination (MMSE). Results The overall self-neglect rate was 86%. The study revealed that self-neglect correlates positively with the degree of disability (p < 0.001) and depressive symptoms (p < 0.001). In contrast, monthly income (p = 0.002) and perceived social support (p = 0.001) were negatively associated with self-neglect. Conclusion During the COVID-19 outbreak, self-neglect has been a serious public health problem among older adults with disabilities. Lower monthly income, decreased physical function, depressive symptoms, and perceptions of poor social support contributed to self-neglect among older adults with disabilities.